The odour fingerprint of bitumen. (8th May 2017) - Autelitano, F.; Garilli, E.; Pinalli, R.; Montepara, A.; Giuliani, F.
Abstract : Bitumen is a very complex material with chemical composition and properties highly dependent on the crude oil source and refinery processes. Several analytical procedures were developed to understand the relationship between bitumen composition, microstructure and physical properties. Nevertheless, these techniques are expensive, time-consuming and involve significant drawbacks. Moreover, advanced research and industrial research have often different purposes and timing perspectives. Several bitumen operators require simpler and more suitable techniques for research and technology development, production and acceptance control and above all polymer modification. This necessity has led the authors to propose a new approach based on the artificial olfactory system (AOS), also known as electronic nose or e-nose. AOS is an instrument consisting of an array of partially selective sensors coupled to a suitable pattern-recognition system capable of recognising complex odours. The warm-up study highlighted the possibility of AOS to discriminate, already at room temperature without the need of sample pre-treatments, between bitumen produced with different origin crude oils and to verify the production stability in the same plant. Thus, these results indicate that the e-nose method may be used for quality assurance and quality control applications and for the fingerprinting of bitumen, showing a number of advantages over classical analytical instruments.